Water Resources Carrying Capacity of Qingshui River Basin Based on System Dynamics Modeling - WU Jia-wei, LI Jin-yan, MA Zhan-cun (长江科学院院报)
This study selects the Qingshui River Basin, the largest first-order tributary of the Yellow River in Ningxia, as the research area. It comprehensively considers the co-development of water resources, socio-economic, and water environment subsystems in this basin. By applying the system dynamics method, we established a system dynamics model of the Qingshui River Basin using Vensim software and set up five different scenarios. Based on historical data from 2006 to 2020, we employed the entropy weighting-TOPSIS method to predict the dynamic changes in water resources carrying capacity under these five scenarios from 2021 to 2030 so as to identify the optimal solution for enhancing the basin’s water resources carrying capacity. Results indicate that the water resources carrying capacity of the Qingshui River Basin remains inferior under the status-quo continuation scenario. The economic-priority, agricultural-priority, and environmental-priority scenarios can only partially alleviate the pressures on socio-economic development, water resources supply and demand, and the water environment. In contrast, the comprehensive and coordinated scenario can comprehensively improve the evaluation indicators of water resources carrying capacity, meeting the requirements for promoting the basin’s sustainable development. This study offers a reference for water resources management and planning in the Qingshui River Basin.